Opacity specification based on visibility ratio and occlusion vector in direct volume rendering. (April 2017) - Li, Lu; Peng, Hu; Chen, Xun; Cheng, Juan; Gao, Dayong
Abstract : Highlights: We present the notion of visibility ratio, which is a quantitative and size independent measure of occlusion. We propose the notion of occlusion vector and feedback process for the interested structure to make the linear feedback process possible. The feedback process of our system is quite similar to alpha blending that users are familiar with. The feedback process of our system is quite similar to alpha blending that users are familiar with. Abstract: Direct volume rendering is widely used in 3-D volume visualization. In recent years, many sophisticated transfer functions have been designed to extract boundaries and structures, such as intensity-gradient histogram and LH histogram. However, it is still tedious and time-consuming to fine-tune the opacity to achieve high quality of visualization. Even with high-quality transfer functions the rendering results may still contain ambiguous information so that users may be misled. Possible reasons are the loss of depth information when a 3-D volume compresses to a 2-D image and information superposition in the form of occlusion while using ray casting or other rendering algorithms. In this paper, we propose the notion of visibility ratio and occlusion vector which are quantitative measures of occlusion based on the front-to-back iteration of ray casting. According to the measures we present a semiautomatic linear feedback mechanism to tweak the pre-designed opacity transfer function. As the opacity refinement can be regarded as alpha color blending that users are familiar with, users could understand occlusion and explore transfer function space intuitively. It is straightforward to integrate our method into other visualization systems based on the data-centric transfer function as an important supplement.